Investigation of IL23R, JAK2, and STAT3 gene polymorphisms and gene–gene interactions in Crohn’s disease and ulcerative colitis in a Turkish population - Can, Güray; Tezel, Ahmet; Gürkan, Hakan; Tozkır, Hilmi; Ünsal, Gülbin; Soylu, Ali Rıza; Ümit, Hasan Celalettin (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Inflammatory bowel diseases are chronic, relapsing, inflammatory conditions. They have a genetic backround resulting in patient susceptibility. The aim of our study is to investigate the involvement of IL23R, JAK2, and STAT3 polymorphisms in inflammatory bowel diseases in a Turkish population. Materials and Methods: Polymorphisms in IL23R (rs11209026), JAK2 (rs10758669), and STAT3 (rs3816769, rs2293152, rs744166, rs957970, rs8074524) were genotyped in 69 Crohn’s disease patients, 157 ulcerative colitis patients, and 89 healthy controls. Results: The presence of (C) in rs10758669, (T) and (TT) in rs957970, and (TT) in rs744166 were found to increase the susceptibility to Crohn’s disease (p=0.049, p=0.016, p=0.010, p=0.035, respectively), while rs2293152 (GC), rs744166 (CT), and rs957970 (CT) provide protection against Crohn’s disease (p=0.007, p=0.043, p=0.043, respectively). While rs2293152 (GC) was protective, rs2293152 (CC) increased the susceptibility to ulcerative colitis (p=0.009, p=0.001). All the polymorphisms were associated with age-at-diagnosis, except rs11209026. Furthermore, rs2293152 was associated with an extension in ulcerative colitis, while rs10758669, rs3816769, rs744166, rs2293152, and rs957970 were associated with the subphenotype in Crohn’s disease. The presence of rs10758669 (AC) was protective against perianal Crohn’s disease (p=0.016). Additionally, rs10758669 and rs2293152 in Crohn’s disease and rs8074524, rs3816769, and rs10758669 in ulcerative colitis were associated with the requirement of immunsuppression. Finally, rs8074524 and rs10758669 in Crohn’s disease and rs11209026 in ulcerative colitis were associated with disease-related operation. Conclusion: This is the first study of the single marker association of IL23R, JAK2, and STAT3 polymorphisms with ulcerative colitis and Crohn’s disease in a Turkish population. It was demonstrated that these polymorphisms may be effective in the etiology of inflammatory bowel disease in this Turkish population.